Acoustic Emission Characteristics and Failure Patterns of Basalt Fiber and Basalt Textile Reinforced Concrete under Flexural Load - Minghao Jia; Kun Qian; Kejing Yu (Journal of Natural Fibers, 2022)
The effects of fiber structure and curing period on the flexural properties of basalt fibers reinforced fine-grained concrete were investigated in this paper. The damage and fracture processes of composites were monitored using acoustic emission technology. The flexural behavior of composites in terms of load-displacement curves, ultimate flexural load, and toughness was studied. The damage and fracture patterns of composites were described using acoustic emission parameters such as ringing count, amplitude, and accumulative energy. In the middle and late periods, basalt textiles outperformed basalt fibers in terms of improving the flexural load of fine-grained concrete. The flexural load improved at first and then decreased as the amount of basalt fibers increased, while the flexural load continued to improve as the amount of basalt textiles increased. Compared with basalt fibers reinforced fine-grained concrete, the flexural load of basalt textiles reinforced fine-grained concrete with 28 days curing period increased by 13.40%, −2.13%, and 75.96%, respectively. In terms of acoustic emission, the basalt textiles reinforced fine-grained concrete released more energy, the intensity and frequency of the acoustic emission signal were higher, and the cumulative ringing count was also greater. The basalt textiles reinforced fine-grained concrete exhibited greater flexural deflection and ductility.